Perubahan Perilaku Hidup Bersih dan Sehat Sebelum dan Selama Pandemi COVID-19 pada Mahasiswa Kedokteran Universitas Muhammadiyah Jakarta - Makruf, Amar; Farhan, Fanny Septiani (Faculty of Medicine, Universitas Andalas, 2021)
Novel Coronavirus (2019-nCoV) is a virus that causes respiratory disease COVID-19 (Coronavirus Disease-2019). COVID-19 can be transmitted through droplets when someone coughs or sneezes. Clean and healthy behavior is one way that can be done to prevent transmission of COVID-19. Objectives: To determined changes in clean and healthy behavior before and during the COVID-19 pandemic in 135 medical students of Muhammadiyah Jakarta University class of 2020. Methods: Data was collected by online questionnaire. The sampling technique was total sampling. Statistical tests were performed by using paired sample t-test. Results: There were changes in clean and healthy behavior before and during the COVID-19 pandemic. Conclusion:Â Clean and healthy behavior was better during the COVID-19 pandemic among respondents.Keywords: Â COVID-19, clean and healthy behavior, questionnaire